Quark and pion condensates at finite isospin density in chiral perturbation theory - Prabal Adhikari; Jens O. Andersen (European Physical Journal C: Particles and Fields, 2020)
Abstract In this paper, we consider two-flavor QCD at zero temperature and finite isospin chemical potential $$μ _I$$ μ I using a model-independent analysis within chiral perturbation theory at next-to-leading order. We calculate the effective potential, the chiral condensate and the pion condensate in the pion-condensed phase at both zero and nonzero pionic source. We compare our finite pionic source results for the chiral condensate and the pion condensate with recent (2+1)-flavor lattice QCD results. Agreement with lattice results generally improves as one goes from leading order to next-to-leading order.